Predicting the effectiveness of community anti‐poaching patrols for conserving threatened wildlife in the Lao PDR. Issue 2 (15th December 2019) - Kragt, Marit E.; Hay, Eric; Scheufele, Gabriela; Bennett, Jeff; Renton, Michael
Abstract: Worldwide, wildlife poaching results in significant losses to biodiversity, especially for species that are most vulnerable and at risk of extinction. While studies that assess the impact of poaching have been conducted, there is limited work that evaluates strategies to reduce poaching pressure, and their subsequent effects on wildlife. We develop a model to predict the effectiveness of a unique community‐led anti‐poaching patrol programme for conserving local wildlife in a biodiversity hotspot in the Lao People's Democratic Republic (Lao PDR). Our model scenarios are based on local villagers' proposals to undertake anti‐poaching patrols. To deal with limited data availability in this region, we develop a flexible modelling framework that can incorporate a range of data sources, including expert opinion. The model can be readily altered by the user if additional data becomes available. The results predict that, without intervention, 14 out of the 19 endangered species investigated are likely to be poached to local extinction over the next 10 years. Implementing anti‐poaching patrols is predicted to protect individual animals and species in the area, although with diminishing marginal benefits as patrol‐efforts increase. Synthesis and applications . We present the first model developed in the Southeast Asia region to examine the effectiveness of community anti‐poaching patrols on protecting wildlife populations. This work is directly linked to an innovative Payments for Environmental Services programme where villagers are being paid for community‐led anti‐poaching patrols. Our model results demonstrate how different patrolling strategies can help to protect vulnerable species, and are being used to determine the payment levels for different patrolling schemes. Abstract : We present the first model developed in the Southeast Asia region to examine the effectiveness of community anti‐poaching patrols on protecting wildlife populations. This work is directly linked to an innovative Payments for Environmental Services programme where villagers are being paid for community‐led anti‐poaching patrols. Our model results demonstrate how different patrolling strategies can help to protect vulnerable species, and are being used to determine the payment levels for different patrolling schemes.